Hubungan Manajemen Waktu dengan Kebiasaan Prokrastinasi Penyusunan Skripsi pada Mahasiswa Keperawatan - Arum Priharnadi; Samsualam; Mappangandro, Andi (Window of Nursing Journal, 2022)
Students who practice the habit of procrastination take longer to complete their study period compared to students who do not procrastinate. Compiling a thesis is one of the important areas but this is often delayed by students. The purpose of this study is to find out whether there is a relationship between time management and the procrastination habit of thesis preparation in students of the nursing science study program of FKM UMI. The research design used is analitic pobservational with a cross sectional study approach. The sample determination was carried out using a total sampling technique with a sample size of 48 respondents. The relationship test was carried out using the Chi- Square statistical test with a meaningfulness level of p ≤ 0.05. The results showed that there was a relationship between time management and the procrastination habit of thesis preparation with a meaningfulness level of p ≤ 0.04. The conclusion of this study is the effective time management of nursing students of the Faculty of Public Health, Universitas Muslim Indonesia as many as 39 people (81.3%) and students who have ineffective time management as many as 9 people (18.7%), nursing students of the Faculty of Public Health, Muslim University of Indonesia who do not procrastinate as many as 40 people (83.3%), and those who carry out the habit of procrastination as many as 8 people (16.7%). It is necessary to conduct further research with other methods and more samples in order to get even more accurate results in the future.